OSCON 2016 : video compilation. (O'Reilly Media, 2016)
"OSCON Austin 2016 was as big as Texas itself with 293 speakers, 149 sessions, 40 half-day tutorials and 15 keynotes. An exploration of "Everything Open Source", the four-day conference was organized into 12 distinct themes with multiple presentations on The New Stuff, Infrastructure, Architecture, Data, In Real Life, Collaboration, Business of OS, Open Source 101, Performance, Hardware, Security, and Leadership. Unsure about the core technologies of OS? Where it's headed? Don't be. Get up on this video horse, push play, and ride. You'll journey across the entire OS range from Linux, MySQL, the LAMP stack, Perl, Python and Ruby on Rails to middleware, applications, cloud computing, and more."--Resource description page.